Relationship Between MR Spectroscopy-Detected Glutamatergic Neurometabolites and Changes in Social Behaviors in a Pilot Open-Label Trial of Memantine for Adults With Autism Spectrum Disorder - Nair, Neetu; Hegarty, John Patrick; Cirstea, Carmen Mihaela; Gu, Meng; Appling, Carrina Brooke; Beversdorf, David Quentin (Frontiers in Psychiatry, 2022)
Background:. The neurobiology underlying ASD is largely unknown but altered neural excitability/inhibitory ratios have been reported. Memantine is an N-methyl-D-aspartate (NMDA) glutamatergic antagonist studied for treatment of core ASD symptoms, with mixed results. We examined whether glutamatergic other neurometabolite levels predicted response to memantine in an exploratory pilot study. Methods: Ten adult participants with ASD underwent proton magnetic resonance spectroscopy (1H-MRS) imaging, before behavioral assessments assessed before and after 12-weeks of open-label memantine. Clinical Global Impressions–Improvement (CGI-I) for social interaction was the primary outcome measure. Point RESolved Spectroscopy (PRESS) quantified concentrations of glutamate+glutamine (Glx), N-acetylaspartate (NAA), creatine+phosphocreatine (Cr+PCr), and myo-inositol (Ins), within left dorsolateral prefrontal cortex (LDLPFC), and right postereolateral cerebellum. LCModel and SPM were used to perform brain tissue segmentation within the regions. Linear hierarchical regression models determined associations between neurometabolite concentrations and behavioral assessment changes using SPSS. Results: Partial correlations controlling for age and gray matter fraction revealed that CGI-I social scores were not correlated with neurometabolite levels. Change in the Social Responsiveness Scale (SRS) scores were related to neurometabolite levels in the LDLPFC. Linear hierarchical regression revealed Glx, Cr+PCr and Ins levels in LDLPFC were predictors of CGI-I social scores. Discussion: Glx did not directly predict response on social outcomes. However, interactions between Glx and measures associated with excitatory neurotransmission, cerebral energy metabolism and glial integrity may explain some of the mixed results reported in previous memantine studies in ASD. Future studies will need to examine these results in a larger sample.